2019
DOI: 10.1016/j.addbeh.2019.106028
|View full text |Cite
|
Sign up to set email alerts
|

‘Someone like me’: User experiences of the discussion forums of non-12-step alcohol online support groups, June 2019

Abstract: Background: Peer support is widely acknowledged to be an important factor in recovery from problem drinking. Many seek this from support groups, including those online. Whilst Alcoholics Anonymous (AA) and other 12-step groups have provided help to many people, some individuals do not find them useful. This paper aims to contribute to the current limited knowledge on non-12-step groups, i.e., those that do not follow the approach of AA. Methods: Twenty-five semi-structured interviews were carried out with user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Findings pertaining to attendance, feasibility, and intervention preference suggest that connecting with someone who has “been there” is a preferred treatment modality that can engender high patient engagement, which is particularly notable for patients with eating disorders, often characterized by high ambivalence about change. Our findings align with a growing body of literature across fields of mental health pointing to the utility of peer connection and relationships in mental health recovery (Collins et al, in press; Naslund, Aschbrenner, Marsch, & Bartels, ; Sanger, Bath, & Bates, ).…”
Section: Discussionsupporting
confidence: 89%
“…Findings pertaining to attendance, feasibility, and intervention preference suggest that connecting with someone who has “been there” is a preferred treatment modality that can engender high patient engagement, which is particularly notable for patients with eating disorders, often characterized by high ambivalence about change. Our findings align with a growing body of literature across fields of mental health pointing to the utility of peer connection and relationships in mental health recovery (Collins et al, in press; Naslund, Aschbrenner, Marsch, & Bartels, ; Sanger, Bath, & Bates, ).…”
Section: Discussionsupporting
confidence: 89%
“…Graham et al's analysis of the 2015 UK Life in Recovery survey results found that there was a significant association between gender and the use of online recovery groups ( 38 ). More nuanced studies support this: Sinclair et al, found that 94% of respondents to their study of Soberistas were female, “overwhelmingly in employment with post-graduate qualifications” [( 39 ), p. 223–4]—a demographic reflected in Sanger et al's study of multiple non-12-step AOSGs ( 40 ). Furthermore, research regarding Dry January ( 34 ) and Hello Sunday Morning ( 41 , 42 ) shows that women are also at the forefront of trying to renegotiate their relationship with alcohol via abstinence challenges.…”
Section: Women's Participation In Online Sobriety Communitiesmentioning
confidence: 98%
“…Studies of non-12-step AOSGs and TAI communities suggest a multitude of reasons why people (particularly women) are increasingly utilising internet platforms, including; flexibility and access ( 40 , 47 , 48 ), accountability ( 48 ), stigma reduction through anonymity ( 39 , 48 , 49 ), specialist information ( 39 , 50 ), support ( 39 , 42 , 51 , 52 ), empowerment ( 53 ), and the value of sharing personal storeys in the written form ( 39 , 49 , 50 , 54 ). Many of these advantages align with the gendered needs of women in recovery outlined within the introduction.…”
Section: Meeting Women's Needs In Recoverymentioning
confidence: 99%
See 2 more Smart Citations